Analysis of the COMPARE-AMI trial: First report of long-term safety of CD133+ cells. (15th November 2020) - Haddad, Kevin; Potter, Brian James; Matteau, Alexis; Reeves, François; Leclerc, Guy; Rivard, Alain; Gobeil, François; Roy, Denis-Claude; Noiseux, Nicolas; Mansour, Samer
Abstract: Background: Data related to long-term safety of intracoronary (IC) injection of CD133+ bone marrow stem cells (BMSC) following an acute myocardial infarction (MI) are still lacking. Methods: COMPARE-AMI is a double-blind, placebo-controlled phase II clinical trial evaluating the safety and efficacy of IC injection of CD133+ enriched hematopoietic BMSC in patients with ST-elevation myocardial infarction (STEMI) and persistent left ventricular (LV) dysfunction following successful primary percutaneous coronary intervention (PCI). Herein, we report outcomes up to ten years of follow-up. Results: Between November 2007 and July 2012, we enrolled 38 patients in our study. Males were 89% and the median age was 50.5 years. Baseline left ventricular ejection fraction (LVEF) was 40.0%, and 90% of lesions were located in the left anterior descending (LAD) artery. The median follow-up time was 8.5 years IQR [7.9, 10.0]. Using Kaplan-Meier methods, MACE-free survival up to 10 years was 77.3% overall. IC injection of CD133+ BMSC was associated with a similar event-free survival rate compared to placebo (87.8% vs. 66.3%, p = .37). Two cancer cases in each group were recorded. No malignant arrhythmias were observed. Conclusions: IC injection of CD133+ BMSC is safe up to 10 years of follow-up. The long-term efficacy needs to be confirmed by a larger randomized trial. Highlights: A reduced LVEF following MI has a higher risk of adverse events despite timely PCI. IC injection of CD133+ BMSC following MI may promote cardiac protective pathways. Safety of these cells was evaluated up to 10 years compared to placebo. IC injection of CD133 + BMSC is safe. CD133+ cells showed a similar MACE-free survival rate as compared to placebo.